Bivalirudin-hydrogel coatings of polyvinyl chloride on extracorporeal membrane oxygenation for anticoagulation - Gao, Wenqing; Shen, Hechen; Chang, Yun; Tang, Qin; Li, Tong; Sun, Di (Frontiers in Cardiovascular Medicine, 2023)
Thromboembolic events associated with extracorporeal membrane oxygenation (ECMO) in clinical treatment are typical. Heparin coating has been widely employed as a surface modification strategy for ECMO tubes. However, its clinical application is often accompanied by unavoidable complications due to its mechanism of action. As a direct thrombin inhibitor with a single target, Bivalirudin (BV) has exhibited a lower incidence of adverse events and superior pharmacokinetic performance compared to heparin. A gelatin methacrylate hydrogel (GelMA) coating layer with BV was successfully synthesized on polyvinyl chloride, and the drug release ratio was close to complete release within 7 days. Simulated extracorporeal circulation experiments using roller pumps in vitro and jugular arteriovenous bypass experiments in rabbits demonstrated its outstanding anticoagulant efficacy. The systemic anticoagulant assay proved that BV hydrogel coating does not affect the coagulation level, and reduces the risk of complications such as systemic bleeding compared to intravenous injection. BV-Coating GelMA hydrogel tube has exhibited good biocompatibility and significantly improved anticoagulant performance, making it an optimal choice for surface materials used in blood-contacting medical devices.